Perencanaan pompa sentrifugal untuk pengisian air boiler dengan kapasitas 0,01 m3/detik daya 15,3 hp dan putaran 1500 rpm - Antonius Edi Efendi Uma Sinaga (Fakultas Teknik dan Ilmu Komputer, 2022)
Pump is a device to move fluid (liquid) from a lower place to a higher place which works on the basis of converting mechanical energy into kinetic energy (hydraulic). The water source used comes from river water and the pump used is a centrifugal pump. This pump needed to serve the filling of boiler water with a steam capacity of 30 tons/hour with a pressure in the boiler drum of 12 kg/cm2. For the capacity of the boiler water filling pump must be greater in the range of 20 – 25%. In this case, for this calculation, 20 % x 30 tons/hour is taken, then the resulting capacity (Q) is 36 tons/hour, or divided by the specific gravity of water, the water capacity will be 0.01 m3/s. Furthermore, to calculate the pump power, first calculate the total head pump, where the pump head consists of the suction pipe head and the pressure pipe head. To calculate the suction head, of course, the losses that occur must first be calculated, such as losses in the length of the pipe and in the pipe fittings. Where the length of the suction pipe is 7 m and the diameter of the suction pipe is 3 inches or 76.2 mm. To obtain the coefficient of friction (f) we must first calculate the Reynolds number (Re), the formula is Re = Vs . ds/v where Vs is the velocity of the water flow in the pipe, which is 3 m/s, ds = 78.2 mm and v is the kinematic viscosity of water, so from the multiplication result, Re = 809920.283 is called turbulent flow. Where the pipe material is selected cast iron with hardness = 0.024. From the distribution of the roughness price and pipe diameter, 0.003 will be obtained, so from the viscosity graph and Re, the coefficient of friction f = 0.025 will be obtained. For further losses in the elbow where the formula is hb = f . Vs/2.g for the coefficient of friction at the elbow is 0.35 while Vs = 3 m/s, so from the multiplication results, the head losses at the elbow hb = 0.16 m, as well as losses at the gate valve and others. The results of the number of lossesabove obtained a total head loss of 1.72 m suction in the same way as well as a total head loss of 123.28 m. Then the total head obtained is 125 m After the total head is obtained, the pump power will be calculated with the formula Np = .g Hp.Q/μp, then 1000.9,81.125.0.01/0.78 = 15,721 Kw(21.07Hp). Motor power obtained by multiplying fc = 1.1 obtained 17.29 Kw. From all these data as a basis for designing a centrifugal pump.